MAIN DIRECTIONS OF SEA FREIGHT DEVELOPMENT IN UKRAINE: FORMATION OF NEW LOGISTICS HUBS - Kuzmenko, О.; Kuzmenko, V.; Bezuhlova, I. (Municipal economy of cities. Series: «Economy science», 2023)
The article addresses the pressing issue of sea freight development in Ukraine, taking into account trends in the logistics industry and the geopolitical situation, including the occupation of the Kherson region by the Russian aggressors. The article aims to identify opportunities and prospects for utilising the Kherson ports to facilitate cargo transportation after the full de-occupation of the region and to study the impact of geopolitical and logistical factors on the development of this industry. Analysis of the state of the Kherson region port infrastructure before the occupation allowed us to identify potential tasks for port modernisation by studying the infrastructure, capacities, and possibilities of the ports. An evaluation of the impact of the geopolitical situation enabled the coordination of the developed logistical routes and prospective logistic hubs in Europe and Turkey. For this purpose, we conducted an analysis of information regarding the occupation of the Kherson region and its influence on logistical flows. Logistical scenarios are in development for post-occupation of the region. The task is to create feasible logistical scenarios for cargo transportation through the Kherson ports, including proposals for the southern and Dnipro–Danube directions. As a result of the research, we formulated recommendations for using the Kherson ports as a key logistical hub for cargo transportation in Ukraine and the region after the de-occupation. The article underscores the importance of developing port infrastructure in the face of geopolitical challenges and provides practical recommendations for optimising cargo transportation through the Kherson ports. Future research may include an analysis of the development of logistical connections between the Kherson ports and other regions of Ukraine, as well as an examination of the impact of geopolitical factors on the efficiency of cargo transportation in the region. In conclusion, this article addresses the critical issue of sea freight development in Ukraine, considering the evolving trends in the logistics industry and the complex geopolitical landscape, particularly in light of the occupation of the Kherson region by the Russian aggressors. The primary objective of this research is to explore opportunities and prospects for leveraging Kherson’s ports to enhance cargo transportation following the eventual de-occupation of the region. Additionally, it aims to investigate the influence of geopolitical and logistical factors on the growth of the maritime industry.